2023
DOI: 10.3389/fpubh.2023.1122626
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and its correlation with anxiety, headache and sleep disorders among medical staff in the Hainan Province of China

Abstract: ObjectiveThis cross-sectional survey aimed to investigate the prevalence of depression among medical staff and its risk factors as well as the association between depression, anxiety, headache, and sleep disorders.MethodsStratified random cluster sampling was used to select medical staff from various departments of four hospitals in Sanya City. The Self-Rating Depression Scale (SDS), Self-Rating Anxiety Scale (SAS), and Pittsburgh Sleep Quality Index (PSQI) were used to quantitatively assess depression, anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
1
0
0
Order By: Relevance
“…The survey results showed that the prevalence of depressive symptoms among employees in Zhejiang Province's public utility places was 17.9%, which was similar to the results among the Chinese labour force in 2016 (17.3%) and in-service employees in 2018 (19.3%) studied by Guoying Zhang [26]. Although the prevalence of depressive symptoms among employees of public utility places is lower compared with the elderly and the highstress occupational groups (44.1-55.2%) [36,37], nearly 20% is still a shocking proportion because these people are the main labour force in society and the spiritual and economic support of a family, and they should be very healthy.…”
Section: Current Status Of Depressive Symptoms and The Observed Facto...supporting
confidence: 81%
“…The survey results showed that the prevalence of depressive symptoms among employees in Zhejiang Province's public utility places was 17.9%, which was similar to the results among the Chinese labour force in 2016 (17.3%) and in-service employees in 2018 (19.3%) studied by Guoying Zhang [26]. Although the prevalence of depressive symptoms among employees of public utility places is lower compared with the elderly and the highstress occupational groups (44.1-55.2%) [36,37], nearly 20% is still a shocking proportion because these people are the main labour force in society and the spiritual and economic support of a family, and they should be very healthy.…”
Section: Current Status Of Depressive Symptoms and The Observed Facto...supporting
confidence: 81%
“…Furthermore, 48 individuals (47.06%) displayed significant anxiety, and 24 individuals (23.53%) suffered from severe depression (Table 2). It is well-established that sleep and mental disorders are interrelated [28]. Although limited evidence links anxiety and depression with ovarian function, we included emotional factors as candidate variables in our investigation.…”
Section: Characteristics Of the Included Participantsmentioning
confidence: 99%
“…The relationship between sleep quality and poor mental health outcomes, such as anxiety and depression, remains uncertain [22]. This implies that poor sleep quality may contribute to the development of anxiety and depression, which is supported by a significant body of literature [23][24][25][26]. Moreover, A recent study utilizing Mendelian randomization methodology has identified insomnia as a causal factor contributing to the development of anxiety [27].…”
Section: Introductionmentioning
confidence: 99%